2010
DOI: 10.1177/0093854810362342
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Personality Characteristics of Predatory, Irritable, and Nonviolent Offenders

Abstract: This article represents an initial attempt to adapt the three most relevant components of Moyer’s animal aggression typology to humans. These include predatory (unemotional, goal-directed), irritable (anger-based), and defensive (fear-based) aggression. As different brain networks are likely involved, the authors hypothesized that executive function and personality tests could differentiate violent from nonviolent criminals and discriminate the types originally classified on the basis of criminal history. Disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 50 publications
5
39
2
Order By: Relevance
“…These subtypes partly correspond with the concepts of proactive and reactive aggression, but are not exactly the same theoretical constructs (Nussbaum, Saint-Cyr, & Bell, 1997). Both Bass and Nussbaum (2010), and Levi et al (2010) found significantly impaired performance in the IGT for both aggressive groups in contrast to non-violent offenders. One of the studies revealed that predatory aggressors performed better on tasks for inhibition than reactive aggressors (Levi et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 81%
See 4 more Smart Citations
“…These subtypes partly correspond with the concepts of proactive and reactive aggression, but are not exactly the same theoretical constructs (Nussbaum, Saint-Cyr, & Bell, 1997). Both Bass and Nussbaum (2010), and Levi et al (2010) found significantly impaired performance in the IGT for both aggressive groups in contrast to non-violent offenders. One of the studies revealed that predatory aggressors performed better on tasks for inhibition than reactive aggressors (Levi et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…Two studies distinguished between predatory and irritable aggression in offenders (Bass & Nussbaum, 2010;Levi et al, 2010). These subtypes partly correspond with the concepts of proactive and reactive aggression, but are not exactly the same theoretical constructs (Nussbaum, Saint-Cyr, & Bell, 1997).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 3 more Smart Citations